“Propuesta de un Manual de Funciones para el Centro de Investigaciones Territoriales (CIT - UNL) de la Universidad Nacional de Loja, período 2024” - Revilla Merchán, Luisa Fernanda (2024)
The research work was carried out at the Territorial Research Center of the National University of Loja (CIT - UNL), which focuses on strengthening territorial development processes and research in areas such as land use planning and management in the southern region of the country. The general objective of the research was to design a functions manual for the CIT - UNL, and the specific objectives were to diagnose the Center's functions, formulate the proposed functions manual, and finally, socialize the proposed manual with the Center's key stakeholders. In order to achieve the objectives, the methodology used was a qualitative approach, under the inductive method, from a non-experimental - transversal research design, with a descriptive - exploratory scope to analyze the information collected. Techniques such as interviews and bibliographic review were used. The interviews were directed to the director of the Center for Territorial Research and to the key actors Analyst Technician I, Teaching Researcher and Research Technician. Finally, the manual of functions was prepared and presented to CIT - UNL collaborators to improve planning, management and territorial development at CIT - UNL, providing clarity in the functions of the collaborators, and facilitating the achievement of the Center's objectives.